URIC ACID PROFILE IN PATIENTS WITH CHRONIC NONSPECIFIC MUSCULOSKELETAL PAIN - Afzal, Naeema; Mahmud, Tafazzul -e-Haque; Jahan, S Shah; Kundi, Salma (Journal of Ayub Medical College Abbottabad, 2003)
Background: The present study was undertaken to determine the uric acid profile in patients with unexplained chronic musculoskeletal complaints, and to establish any possible causal role for altered uric acid profile in such patients. Method: A comparative study of 36 patients and 36 controls of both sexes and ages between 25-60 years was carried out at Shaikh ZayedHospital, Lahore from November 2001-May 2002. Patient included were those who had at least 4-24 weeks duration of complaints. Uric acid profile for serum uric acid, uric acid excretion, uric acid clearance and total uric acid production was done. Additional tests included renal functions test, liver function test, cardiac enzymes, haematology and serology to exclude other underlying causes of complaints. Results: Mean serum uric acid levels were higher in patients as compared to controls (p=0.05), with 9 (25%) patients showing hyperuricemia. Uric acid clearance (female patients 5.86+0.42 ml/min, female controls 8.06+0.24 ml/min) and daily uric acid excretion (female patients 412.38+28.52 mg/24 hours, female controls 487.79+18.64 mg/24 hours) in female patients was significantly lower than control females (P=0.034 and P<0.001 respectively). Twenty patients (55.55%, 3 males and 17 females) were classified as under excretors of uric acid, while there were no under excretors in the control group (p<0.001). Conclusion: We conclude that abnormalities of uric acid profile, particularly under excretor status may be an underlying biochemical abnormality in a significant number of patients. Female patients appear more predisposed to abnormal uric acid profile such as hyperuricemia and under excretor status. Key words: Uric acid, musculoskeletal diseases, gout.